Exercise and diabetes - De Feo, Pierpaolo; Di Loreto, Chiara; Ranchelli, Anna; Fatone, Cristina; Gambelunghe, Giovanni; Lucidi, Paolo; Santeusanio, Fausto (Acta Biomedica Atenei Parmensis, 2006)
Physical activity activates has acute and chronic effects on glucose, lipid and protein metabolism. In type 1 diabetic subjects, the lack of the physiological inhibition of insulin secretion during exercise results in a potential risk of hypoglycemia. On the other hand, exercise-induced activation of counterregulatory hormones might trigger an acute metabolic derangement in severe insulin-deficient subjects. Thus, diabetic patients, before starting exercise sessions, must be carefully educated about the consequences of physical activity on their blood glucose and the appropriate modifications of diet and insulin therapy. Long-term effects of regular exercise are particularly advantageous for type 2 diabetic patients. Regular aerobic exercise reduces of visceral fat mass and body weight without decreasing lean body mass, ameliorates insulin sensitivity, glucose and blood pressure control, lipid profile and reduces the cardiovascular risk. For these reasons, regular aerobic physical activity must be considered an essential component of the cure of type 2 diabetes mellitus. In this regard, individual behavioral strategies have been documented to be effective in motivating sedentary type 2 diabetic subjects to the adoption and the maintenance of regular physical activity.